2021
DOI: 10.30773/pi.2020.0289
|View full text |Cite
|
Sign up to set email alerts
|

“Reading the Mind in the Eyes Test”: Translated and Korean Versions

Abstract: Objective The Reading the Mind in the Eyes Test (RMET) was developed by using Caucasian eyes, which may not be appropriate to be used in Korean. The aims of the present study were 1) to develop a Korean version of the RMET (K-RMET) by using Korean eye stimuli and 2) to examine the psychometric properties of the Korean-translated version of the RMET and the K-RMET.Methods Thirty-six photographs of Korean eyes were selected. A total of 196 (101 females) healthy subjects were asked to take the Korean-translated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Conversely, there is considerable variation in reported levels of internal consistency based on Cronbach's alpha (α), which is the most frequently reported measure of internal consistency for the RMET (Kittel et al, 2021). While some studies have reported moderate (e.g., Kuczynski et al, 2020;Soker-Elimaliah et al, 2020) to high levels of internal consistency (e.g., Ozturk et al, 2020;Israelashvili et al, 2020), other studies have reported low levels of internal consistency (e.g., Giordano et al, 2019;Khorashad et al, 2015;Koo et al, 2021;Meyer & Shean, 2006;Vellante et al, 2013). A recent meta-analysis of the psychometric properties of the RMET reported an acceptable α value of .73 (95% confidence interval [CI] [.65,.79]) based on 21 effect sizes (Kittel et al, 2021).…”
Section: The Rmetmentioning
confidence: 99%
“…Conversely, there is considerable variation in reported levels of internal consistency based on Cronbach's alpha (α), which is the most frequently reported measure of internal consistency for the RMET (Kittel et al, 2021). While some studies have reported moderate (e.g., Kuczynski et al, 2020;Soker-Elimaliah et al, 2020) to high levels of internal consistency (e.g., Ozturk et al, 2020;Israelashvili et al, 2020), other studies have reported low levels of internal consistency (e.g., Giordano et al, 2019;Khorashad et al, 2015;Koo et al, 2021;Meyer & Shean, 2006;Vellante et al, 2013). A recent meta-analysis of the psychometric properties of the RMET reported an acceptable α value of .73 (95% confidence interval [CI] [.65,.79]) based on 21 effect sizes (Kittel et al, 2021).…”
Section: The Rmetmentioning
confidence: 99%
“…Indeed, the RMET has been criticized several times for not being a pure measurement of a single factor (Higgins et al, 2022;Kittel et al, 2022;Olderbak et al, 2015). At the same time, it showed high test-retest reliability (Fernández-Abascal et al, 2013;Jankowiak-Siuda et al, 2016;Koo et al, 2021;Vellante et al, 2013) and good correlations with convergent tests (Kim et al, 2022;Schlegel et al, 2019; the present study). Similarly, the STEU has been criticized for containing many suboptimal items (Allen et al, 2014).…”
Section: Discussionmentioning
confidence: 43%
“…For example, Jankowiak-Siuda et al ( 2016) reported a Cronbach's alpha equal to 0.67 for the Polish version of the RMET and a test-retest reliability of 0.89. Koo et al (2021) found values of, respectively, 0.54 and 0.78 for the Korean version, and Vellante et al (2013) reported values of 0.60 and 0.83 for the Italian version. Fernández-Abascal et al (2013) reported a 1-year test-retest reliability of 0.63 for the Spanish version.…”
Section: Introductionmentioning
confidence: 95%
“…In the K-RMET ( Koo et al, 2021 ), a photograph of a Korean person’s face was used based on the procedure in the original the RMET ( Baron-Cohen et al, 2001 ). The same age (young, middle, elder), sex, and pupil orientation were applied as in the original version of the RMET, except for ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…The RMET has been translated into various languages and is being used in the study of clinical populations with ToM deficit ( Kettle et al, 2008 ; Bora et al, 2009 ; Peñuelas-Calvo et al, 2019 ). Recently, the Korean version of the RMET (K-RMET) was developed to overcome the limitation that the existing RMET may not reflect racial and cultural characteristics well, and in a study comparing the psychometric properties of the RMET and the K-RMET, acceptable reliability and validity were reported ( Koo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%